Duration of carbapenemase-producing enterobacteriaceae carriage in hospital patients - Mo, Y; Hernandez-Koutoucheva, A; Musicha, P; Bertrand, D; Lye, D; Ng, OT; Fenlon, SN; Chen, SL; Ling, ML; Tang, WY; Barkham, T; Nagarajan, N; et al. (Centers for Disease Control and Prevention, 2020)
To determine the duration of carbapenemase-producing Enterobacteriaceae (CPE) carriage, we studied 21 CPE carriers for »1 year. Mean carriage duration was 86 days; probability of decolonization in 1 year was 98.5%, suggesting that CPE-carriers' status can be reviewed yearly. Prolonged carriage was associated with use of antimicrobial drugs.